The role of parents in behavioral treatment for adolescent obesity: design and rationale for the TEENS+ randomized clinical trial - Melanie K. Bean; Jessica Gokee LaRose; Edmond P. Wickham; Hollie A. Raynor; Laura Caccavale; Ronald K. Evans; Laura M. Thornton; Sarah Farthing; Ashley Mendoza; Suzanne E. Mazzeo (BMC, 2023)
Abstract Background There is an urgent need for innovative approaches to adolescent obesity treatment, particularly among individuals from racially and ethnically marginalized backgrounds, who face increased risk of obesity and its associated morbidity and mortality. There is a particular dearth of research on the long-term efficacy of adolescent obesity treatments. Further, research and clinical practice guidelines consistently recommend parents' inclusion in their adolescents' obesity treatment, yet the most effective strategy to engage parents in adolescent obesity treatment remains unclear. Towards that end, this investigation will conduct a fully-powered, randomized clinical trial to examine the efficacy of two distinct approaches to involving parents in their adolescents' obesity treatment. Methods Participants will be 210 12-16 year old adolescents (body mass index [BMI]≥85th percentile) and parents (BMI≥25 kg/m2) with overweight or obesity. Dyads will be randomized to one of two 4-month treatments: 1) TEENS+Parents as Coaches (PAC), engaging parents as helpers in their child's weight management via parent skills training based on authoritative parenting, or 2) TEENS+Parent Weight Loss (PWL), engaging parents in their own behavioral weight management. All adolescents will participate in the TEENS+ protocol, which includes nutrition education with dietary goals, supervised physical activity, and behavioral support, and integrates motivational interviewing to enhance treatment engagement. Assessments of anthropometrics, dietary intake, physical activity, parenting and home environment variables will be completed at 0, 2, 4, 8, and 12 months with the primary endpoint at 12-month follow-up. Discussion Results of this investigation have the potential to significantly advance science in this area and ultimately inform clinical practice guidelines related to the role of parents in adolescent obesity treatment. Trial registration Clinicaltrials.gov NCT03851796. Registered: February 22, 2019.